Critical review of ‘pentafecta’ outcomes after robot‐assisted laparoscopic prostatectomy in high‐volume centres - Patel, Vipul R.; Abdul‐Muhsin, Haidar M.; Schatloff, Oscar; Coelho, Rafael F.; Valero, Rair; Ko, Young H.; Sivaraman, Ananthakrishnan; Palmer, Kenneth J.; Chauhan, Sanket (BJU international, 2011)
What's known on the subject? and What does the study add? We have earlier proposed ‘pentafecta’ as an ideal outcome assessment tool after robotic prostatectomy instead of the classically used ‘tritecta’. This was done to meet the demands and expectations of the prostate cancer patients from minimally‐invasive surgical techniques. This article reviews each of the five arms of ‘pentafecta’ outcomes after robotic prostatectomy performed in high volume centres. • Historically, the ideal outcome of radical prostatectomy (RP) has been measured by achievement of the so‐called ‘trifecta’, or the concurrent attainment of continence and potency with no evidence of biochemical recurrence. However, in the PSA era, younger and healthier men are more frequently diagnosed with prostate cancer. Such patients have higher expectations from the advanced minimally invasive surgical technologies. Mere trifecta is no longer an ideal outcome measure to meet the demands of such patients. • Keeping the limitations of trifecta in mind, we have earlier proposed a new method of outcomes analysis, called the ‘pentafecta’, which adds early complications and positive surgical margins (PSMs) to trifecta. • We performed a Medline search for articles reporting the complications, PSM rates, continence, potency and biochemical recurrence after robot‐assisted RP. Related articles were selected and individual outcomes were reviewed.